Fracture energy of micro crystalline cellulose - Carbon nanotubes reinforced hybrid cementitious composites - Alshaghel, A. (2018)
In the present research, the influence of hybrid reinforcements, i.e. micro crystalline cellulose (MCC)-mul- ti-walled carbon nanotubes (MWCNTs) was investigated on the fracture energy of cementmatrix.The cemen- titious composites were developed by preparing dispersion of MCC-CNT in aqueous medium with the help of two differentsurfactants: cetyltrimethylammonium bromide (CTAB) and Pluronic F-127 and ultrasonic energy.The prepared aqueous suspensions of MCC-CNT were subsequently used to reinforce cement matrix and the fracture energy of reinforced composites was characterized. According to the experimental results, the fracture energy increased strongly (up to 85%) with the use of 0.5%MCC-0.3%CNT as reinforcements with respect to cement. The defoamer concentration has also played an important role in the fracture energy of cement composites.